Drug delivery behavior of magnetic composite: In vitro study (Bangladesh Journal of Medical Science, 2024)
Background One method for delivering the medication to the intended location and achieving the desired therapeutic effect is controlled drug release. Compared to typical release systems, controlled medication release systems offer fewer potential adverse effects and can increase patient comfort by prolonging the time intervals between drug intakes. Expanded perlite modified composite were used as drug carrier materials in the current investigation because of its excellent adsorption capability.Aim: Using magnetic poly(hydroxyethylmethacrylate-expanded perlite) (m-p(hema-ep)) composite material, doxorubicin release was examined in this work.Methodolgy First, a magnetic p(hema-ep) composite was created for this purpose and examined using SEM, FTIR, and swelling tests. The medication doxorubicin served as a model. Tests for reusability were conducted. The synthesized magnetic p(hema-ep) composite was shown to be capable of being recycled ten times without losing effectiveness. On the C6 cell line, the material and the material that had been loaded with doxorubicin were subjected to cytotoxicity tests under magnetic field.Results The impacts of variables like pH, time, temperature, on drug release were examined as a consequence of the characterisation procedure. The ideal release parameters were found to be 80% release at pH 4.5, 70% release is seen at 7.4, and temperature 22 °C, under magnetic field.Conclusion: The anti-cancer medication doxorubicin (Dox) was used as a model drug because it is widely used in cancer treatment and is simple to quantify using methods like UV-visible spectroscopy. There are enhanced doxorubicin release under magnetic field.  Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 666-675